Thermal And Mechanical Properties of Regenerated Nanocellulose Reinforced Polylactic Acid Composites: A Systematic Review - Nor, Nurhanani; Ahmad, Mazatusziha; Roslan, Mohd Nazrul (Progress in Engineering Application and Technology, 2022)
Most of the composite film is derived from unnaturally sourced and non-recyclable materials which in turn leads to the development of biodegradable film from cellulose as replacement. Regenerated nanocellulose (NC) is produced by converting natural nanocellulose to soluble cellulose derivatives and dissolving in ILs solution. Thus, the main objective of the study was to analyze the effect of different category of nanocellulose and size on thermal and mechanical properties of polylactic acid (PLA) composites. Further, the effect of nanocellulose on thermal stability and mechanical properties of poly lactic acid (PLA) composites was investigated. In this study, PRISMA method has been applied to identify accurate and reliable articles. The qualitative analysis covers 20 Systematic Review studies. The size of nanocellulose and degree of crystallinity of the composites were important factors for improvement of mechanical and thermal stability of the composites. Composite with good interfacial adhesion and cellulose distribution between PLA and NC results to the high mechanical properties. In conclusion, modification by ILs shows enhancement in the thermal and mechanical properties of NC/PLA composite. The nanocellulose type and size greatly affects these properties. Further, composite with higher thermal degradation temperature (Tonset and Tmax), results in better thermal stability. Thus, systematic review from the research provides comprehensive information in order to determine the effectiveness of regenerated nanocellulose film as reinforcement agent in PLA composite.